Development of Canva-based Smart Apps Creator Media to Improve High School Students’ Numeric Ability - Yuni Nurherliyani; Nani Ratnaningsih; Diar Veni Rahayu (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2025)
This research aims to describe the procedures for developing Canva-based digital Smart Apps Creator media and analyze the effectiveness of Canva-based digital Smart Apps Creator media and increasing numeric abilities. The subjects in this research were 21 students class XI SMA 1 Pasundan. This research uses the ADDIE Research and Development (R&D) model through the Analysis, Design, Development, Implementation and Evaluation stages to obtain valid and practical products. Data collection techniques in this research are through observation, structured interviews, questionnaires and numeric ability tests. The instruments used in this research were material expert validation sheets, media expert validation sheets, user response questionnaires, and numeric ability test. Canva-based digital Smart Apps Creator media value analysis from validators obtained results of 100% for material experts in the high or very valid category, results from media experts were 100% in the high or very valid category, and index values ??from material experts were 100% in the high or valid category. The effectiveness obtained from the N-gain calculation results obtained an average of 0.68 in the medium category so that the use of Canva-based digital Smart Apps Creator media is effectively used to improve students' numeric abilities.